(3cfR GdCNjGQ aj eYQaI GdSjQ hGdCNHGQs - (3YeGO GdOjf EOQjS Hf Ydj Hf YHO Gddg GdjeGfi,J (B714 (3g` s
(3ChdgG (B:s
(3jHOC ef ebJd Ydi Hf CHj WGdH SfI (B40 (3g` s
(3BNQgG (B:s
(3jfJgi Edi MhGOK SfI (B290 (3g` Je GdLRA GdKGdK ef cJGH cfR GdNjGQ s
(3GdehLhO efg eLdO LGA HChdg (B: (3Cfg ai GdbSe GdChd ef GdLRA GdKGfis
(3HChdg JedcGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B246 s
Keywords: (3GdJGQjNs